Supplementation of ZnSO4 and Zn-Cu Isoleucinate in Ration to Improve Growth and Body Immunity of Young Male Bali Cattle - Hartati, E; Saleh, A; Sulistijo, ED; Ratuwaloe, JJA (ANIMAL PRODUCTION, 2012)
Abstract. An experiment was conducted to evaluate the supplementation of zinc sulphate and Zn-Cu isoleucinate in the local feeds basal diet of young male Bali cattle. The experimental design used was randomized completely block design. The experimental animal were randomly assigned into four group of treaments diet were formulated as: R0= 60% ammoniated âkumeâ grass standinghay + 40% concentrate; R1 = R0 + 150 mg ZnSO4.kg-1 DM concentrate + 1 % Zn-Cu isoleucinate; R2 = R0 + 150 mg ZnSO4.kg-1 DM concentrate + 2 % Zn-Cu isoleucinate; R3 = R0 + 150 mg ZnSO4.kg-1 DM concentrate + 3 % Zn-Cu isoleucinate. The basal diet consisted of ammoniated âkumeâ grass standinghay, whileÂ  concentrate consisted of corn meal, rice bran, coconut cake, fish meal, lemuru oilÂ  and premix. The crude protein content of basal diet was 17%, while total digestible nutrients (TDN) was 78%. The supplementation of zinc sulphate and and Zn-Cu isoleucinate in the diet did not increase significantly crude protein consumption, zinc and cuprum concentration, N and energi retention. However supplementation zinc sulphate and Zn-Cu isoleucinate increase significantly dry matter, energy, zinc and cuprum consumption, zinc and cuprumÂ  absorbtion, phosphatase alkaline, growth and imonoglobulin concentration of young male Bali cattle. The highest daily gain (0.721.day-1) was achieved at level of ZnSO4 and Zn-Cu isoleucinate supplementation of 150 mg ZnSO4 kg-1 concentrate and 2% Zn-Cu isoleucinate kg-1 diet.Â Key words: Bali cattle, Zn-SO4, Zn-Cu isoleucinate, growth, immunoglobulin Â Abstrak. Penelitian dilakukan untuk mengevaluasi penambahan seng sulfat dan isoleusinate Â Zn-Cu dalam pakan lokal basal pada sapi Bali jantan muda.Â  Rancangan percobaan yang digunakan adalah rancangan acak kelompok.Â  Hewan percobaan secara acak dibagi menjadi empat kelompok perlakuan pakan yaitu R0 = 60% rumputÂ  âkumeâ hay teramoniasi + 40% konsentrat, R1 = R0 + 150 mg ZnSO4 kg-1 DM konsentrat + 1% isoleusinate Zn-Cu, R2 = R0 + 150 mg ZnSO4 kg-1 DM konsentrat + 2% isoleusinate Zn-Cu, R3 = R0 + 150 mg konsentrat ZnSO4 kg-1 DM + 3% isoleusinate Zn-Cu.Â  Pakan basal terdiri dari rumputÂ  "kume" hay teramoniasi, sedangkan konsentrat terdiri dari tepung jagung, dedak padi, bungkil kelapa, tepung ikan, minyak lemuru dan premix.Â  Kandungan protein kasar pakan basal adalah 17%, sedangkan total nutrisi tercerna (TDN) adalah 78%.Â  Penambahan seng sulfat dan dan isoleusinate Zn-Cu dalam pakan tidak secara signifikan meningkatkan konsumsi protein kasar, seng dan konsentrasi tembaga, N dan retensi energi.Â  Namun penambahan seng sulfat dan isoleusinate Zn-Cu secara signifikan meningkatkan bahan kering, energi, seng dan konsumsi tembaga, penyerapan seng dan tembaga, basa fosfatase, pertumbuhan dan konsentrasi imunoglobulin pada sapi Bali muda jantan. Pertambahan bobot badan harian tertinggi (0.721 kg day-1) yang dicapai pada tingkat penambahan ZnSO4 dan Zn-Cu isoleusinate 150 mg ZnSO4 kg-1 konsentrat dan 2% Zn-Cu isoleusinate kg-1 pakan. Kata kunci: sapi Bali, Zn-SO4, Zn-Cu isoleusinate, pertumbuhan, imunoglobulinÂ E Hartati et al/Animal Production 14(3):180-186, September 2012